The Effect of Using Black Box Ai to Improve Web Programming Skills of Informatics Education Students - Banung, Floriana Letni; Sogen, Maria Magdalena Beatrice; Ndao, Angelo Fransisco Daga; Tunu, Sherwin Gainell; Koa, Ayu Desita (JUPE : Jurnal Pendidikan Mandala, 2025)
Student   often   face   challenges   or   difficulties   in   creating   attra   web   interfaces,particularly   in   understanding   code   and   finding   suitable   coding   references.   This   study   aims   to   determine   the   impact   of   using   Blackbox.AI   in   supporting   seventh-semester   students   of   the   informatics   Education   study   program   at   Universitas   Citra   Bangsa   in   enahancing   their   web   programming   skills   approach   with   data   collected   were   conducted   using   observation   sheets   to   directly   monitor   the   students’   skill   development   in   independently   completing   web   programming   projects.   The   coolected   data   were   analyzed   using   descriptive   statistics   and   significance   testing.   The   results   of   the   study   indicate   that   the   use   of   Blackbox.AI   has   a   positive   and   significant   impact   on   improving   students’   web   programming   skills.   Students   found   it   easier   to   search   for   coding   references,   produced   more   attractive   web   designs,   and   developed   better-structured   layouts.   Furthermore   ,   students   expressed   high   satisfaction   with   the   outcomes   of   their   proggramming   tasks.   Based   on   the   questionnaire   results,   the   majority   of   students   stated   that   the   use   of   Blackbox.AI   greatly   assisted   them   in   understanding   both   the   concepts   and   practices   of   web   programming.